Management and Structural Aspects of Creation of Sustainable Smart Cities - Batayneh, Sief Addeen M. Mousa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
In light of the exponential rate at which urbanization is accelerating, the smart city concept has gained more attraction worldwide. Smart cities use the latest technologies, sensors, and various monitoring tools in their infrastructure and smart buildings and adopt green sustainable practices in all of their sectors to improve their operational efficiency, sustainability, safety, and disaster resilience while providing the best access to different services and enhancing the quality of life of their citizens. To some extent, the smart city movement has been limited to developed countries, primarily due to several obstacles that may prevent developing countries from implementing smart city initiatives successfully. The research in smart cities initiative, especially in the field of civil engineering is relatively new and is developing rapidly and continuously and is expanding to include more areas in construction and building techniques. The aim of this study is to identify the key factors affecting smart cities from sustainability and disaster management aspects and propose some strategies for improving the more effective factors. For the identification of more important factors a Strengths-Weaknesses-Opportunities-Threats (SWOT) analysis is used. First, a questionnaire survey technique is used to determine the relative importance of these factors. Then, a TOWS matrix is conducted to find the relationship between the SWOT's external and internal factors and draw strategies accordingly. Specifically, this thesis aims to draw strategies for developing countries to take advantage of smart cities' strengths and opportunities while minimizing their weaknesses and threats in two areas of sustainability and disaster management.

ÖZ: Kentsel dönüşümün hızla artan üstel oranında, akıllı şehir kavramı küresel düzeyde daha fazla ilgi çekmeye başlamıştır. Akıllı şehirler, altyapılarında ve akıllı binalarında en son teknolojileri, sensörleri ve çeşitli izleme araçlarını kullanırken, tüm sektörlerinde yeşil sürdürülebilir uygulamaları benimsemekte ve işletme verimliliği, sürdürülebilirlik, güvenlik ve felaket direncini artırmayı amaçlamaktadır. Aynı zamanda vatandaşlarına farklı hizmetlere en iyi erişimi sağlayarak yaşam kalitesini artırmaktadır. Akıllı şehir hareketi, belirli engeller nedeniyle gelişmekte olan ülkelerde uygulama zorlukları yaşandığı için belirli ölçüde gelişmiş ülkelerle sınırlı kalmıştır. Özellikle inşaat mühendisliği alanındaki akıllı şehir girişimi araştırmaları oldukça yeni ve hızlı bir şekilde gelişmektedir ve sürekli olarak genişlemektedir; inşaat ve yapı teknikleri gibi daha fazla alanı içermektedir. Bu çalışmanın amacı, akıllı şehirleri sürdürülebilirlik ve felaket yönetimi açılarından etkileyen temel faktörleri belirlemek ve daha etkili faktörleri geliştirmek için bazı stratejiler önermektir. Daha önemli faktörlerin belirlenmesi için Güçlü Yönler-Zayıf Yönler-Fırsatlar-Tehditler (SWOT) analizi kullanılmıştır. İlk olarak, bu faktörlerin göreceli önemini belirlemek için anket tekniği kullanılmıştır. Ardından, SWOT'un dışsal ve içsel faktörleri arasındaki ilişkiyi bulmak ve buna göre stratejiler çizmek için bir TOWS matrisi uygulanmıştır. Sonuç olarak, bu tez gelişmekte olan ülkelerin sürdürülebilirlik ve felaket yönetimi alanlarındaki zayıf yönlerini ve tehditlerini en aza indirirken akıllı şehirlerin güçlü yönlerinden ve fırsatlarından faydalanmalarını sağlayacak stratejiler çizmeyi amaçlamaktadır.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2023. Supervisor: Prof. Dr. Mahmood Hosseini.
Keywords: Civil Engineering Department; Sustainable urban development; City Planning; Cities and towns--Technological innovations; Smart City, Civil Engineering, Sustainability, Disaster Resilience, SWOT Analysis, TOWS, Information and Communication Technologies, Internet of Things